2013
DOI: 10.1186/1550-2783-10-37
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofMagnolia officinalisandPhellodendron amurense(Relora®) on cortisol and psychological mood state in moderately stressed subjects

Abstract: BackgroundMagnolia (Magnolia officinalis) and Phellodendron (Phellodendron amurense) barks are medicinal plants commonly used as traditional remedies for reducing stress and anxiety. Modern dietary supplements are intended to induce relaxation and reduce stress as well as stress-related eating. Previous studies have shown the combination of Magnolia/Phellodendron (MP) to reduce both cortisol exposure and the perception of stress/anxiety, while improving weight loss in subjects with stress-related eating. Compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…HDACi, with comprehensive anti-tumor effectiveness, are currently undergoing clinical trials to treat several solid and hematologic cancers [1,17]. Various HDACi, such as TSA and romidepsin, are generally well tolerated by cancer patients [38,47]. However, some acute toxicities and side effects, such as transient cytopenias, fatigue, and gastrointestinal upset, are still inevitable in clinical treatment after their long-term usage [17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…HDACi, with comprehensive anti-tumor effectiveness, are currently undergoing clinical trials to treat several solid and hematologic cancers [1,17]. Various HDACi, such as TSA and romidepsin, are generally well tolerated by cancer patients [38,47]. However, some acute toxicities and side effects, such as transient cytopenias, fatigue, and gastrointestinal upset, are still inevitable in clinical treatment after their long-term usage [17].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, multifunctional antitumor agents with tolerable toxicities would be promising strategies for chemotherapeutics. M. officinalis, an herbal medicine with antidepressant and anti-inflammatory effects, has been used for 2000 years in China to treat diarrhea, stroke, asthma, and anxiety [36][37][38]. PM, which is composed of phenolic compounds extracted from M. officinalis, elicits antitumor effects on many cancers [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge no current human studies of the plant for anxiety to date, other than investigations within a herbal combination formula. Although combination formulas of various phytomedicines have demonstrated efficacy for reducing anxiety in humans (e.g., "Relora"; Talbott, Talbott, & Pugh, 2013), the extent to which the observed anxiolytic effects are due to individual components cannot be established. Further, it is recognised that formulas that combine multiple active ingredients may be synergistically more effective-acting through independent but complimentary pathways to confer maximal effects (Bourin, Bougerol, Guitton, & Broutin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to be useful for symptoms of osteoarthritis and shows potential as a neuroprotective agent in Alzheimer’s disease (40, 41). Relora® (Next Pharmaceuticals, Salinas CA) is a proprietary formulation of Phellodendron amurense bark extract standardized to berberine and is believed to reduce stress and anxiety (42). Using activity-guided fractionation of Nexrutine®, we found that butanol fraction (F3) recapitulates the anti-proliferative and NF-κB inhibitory activity of the extract.…”
Section: Nexrutine®mentioning
confidence: 99%